Post exposure prophylaxis for occupational and non occupational exposure to HIV in a tertiary care hospital in central Nepal - Shrestha, Rakshya; Sharma, Sashi; Khadga, Prem; Sayami, Matina; Chitrakar, Uma; Dhungana, Govinda Prasad (Journal of Advances in Internal Medicine, 2018)
Introduction: Post exposure prophylaxis (PEP) to HIV is the short term use of prescribed dose of antiretroviral therapy among persons exposed to high risk behaviors in order to prevent them from HIV infection. While occupationally exposed cases among health care workers are the major target of PEP, it is equally applicable to non occupational exposure to HIV including sexually exposed cases. This study was carried out to know the current scenario of PEP for HIV in terms of various determinants/ risk factors and outcomes of HIV positivity after prophylaxis. Methods: A prospective study was carried out by Antiretroviral therapy center of Tribhuvan University Teaching Hospital. The study period was between August 2006 and September 2016. Altogether 50 cases exposed to known HIV seropositive persons were included in this study. Results: The majority of the occupationally exposures were interns (48.6%), followed by staff nurse (18.9%), CMLT student (13.5%), hospital staff (10.8%) and resident doctor (8.1%). Majority (70.3%) were exposed to needle prick injury. Six-month follow-up showed zero seroconversion for HIV ELISA among the exposed cases. Conclusion: Intern constituted the greater proportion of health care workers exposed to accidental needle stick injury. Timely administration of prophylaxis might have resulted zero seroconversion for HIV ELISA among the exposed cases.